Implementation of Antimicrobial Stewardship Policies in U.S. Hospitals: Findings from a National Survey - Pogorzelska-Maziarz, Monika (Infect Control Hosp Epidemiol, 2015)
OBJECTIVE: To describe the use of antimicrobial stewardship policies and to investigate factors associated with implementation in a national sample of acute care hospitals. DESIGN: Cross-sectional survey. PARTICIPANTS: Infection Control Directors from acute care hospitals participating in the National Healthcare Safety Network (NHSN). METHODS: An online survey was conducted in the Fall of 2011. A subset of hospitals also provided access to their 2011 NHSN annual survey data. RESULTS: Responses were received from 1,015 hospitals (30% response rate). The majority of hospitals (64%) reported the presence of a policy; use of antibiograms and antimicrobial restriction policies were most frequently utilized (83% and 65%, respectively). Respondents from larger, urban, teaching hospitals and those that are part of a system that shares resources were more likely to report a policy in place (P < .01). Hospitals located in California were more likely to have policy in place than in hospitals located in other states (P = .014). CONCLUSION: This study provides a snapshot of the implementation of antimicrobial stewardship policies in place in U.S. hospitals and suggests that statewide efforts in California are achieving their intended effect. Further research is needed to identify factors that foster the adoption of these policies.